Biological Control of Root-Knot Nematodes by Organic Acid-Producing Lactobacillus brevis WiKim0069 Isolated from Kimchi - Seo, Hye Jeong (Plant Pathol J, 2019)
Root-knot nematodes (RKNs) are among the most destructive plant-parasites worldwide, and RKN control has been attempted mainly using chemical nematicides. However, these chemical nematicides have negative effects on humans and the environment, thus necessitating the search for eco-friendly alternative RKN control methods. Here, we screened nematicidal lactic acid bacteria (LAB) isolated from kimchi and evaluated their efficacy as biocontrol agents against RKNs. Of 237 bacterial strains, Lactobacillus brevis WiKim0069 showed the strongest nematicidal activity against the second-stage juveniles (J2) of Meloidogyne incognita, M. arenaria, and M. hapla and inhibited the egg hatch of M. incognita. The culture filtrate of WiKim0069 had a pH of 4.2 and contained acetic acid (11,190 μg/ml), lactic acid (7,790 μg/ml), malic acid (470 μg/ml), and succinic acid (660 μg/ml). An artificial mixture of the four organic acids produced by WiKim0069 also induced 98% M. incognita J2 mortality at a concentration of 1.25%, indicating that its nematicidal activity was derived mainly from the four organic acids. Application of WiKim0069 culture filtrate suppressed the formation of galls and egg masses on tomato roots by M. incognita in a dose-dependent manner in a pot experiment. The fermentation broth of WiKim0069 also reduced gall formation on melon under field conditions, with a higher efficacy (62.8%) than that of fosthiazate (32.8%). This study is the first report to identify the effectiveness of kimchi LAB against RKNs and to demonstrate that the organic acids produced by LAB can be used for the RKN management.